STRATEGI PEMERINTAH KOTA PEKANBARU DALAM MENDISTRIBUSIKAN PANGAN DI MASA PANDEMI COVID-19 TAHUN 2020 - Setiawan, Muhamad Adi; Febrina, Rury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The Covid-19 (Corona Virus Disease-19) pandemic has hit the world since the end of 2019 then this virus entered Indonesia since the beginning of 2020. For approximately 2 years the Covid-19 Pandemic has caused many disasters in various sectors of life, one of which is the food sector. The impact that occurs is ranging from fluctuations in food prices to disruption of food distribution due to various policies implemented by the government. Therefore, the Pekanbaru City Government through the Food Security Office is building community food security with three strategies to anticipate food insecurity in emergency response efforts during the Covid-19 Pandemic. The Covid-19 pandemic is still in a high category but food production and distribution activities continue to run. This research aims to find out the strategy of the Government of Pekanbaru inining food security during the Covid-19 pandemic and what factors hinder the Government strategy in keeping food security in the time of the COVID-19 Pandemic in 2020. This research uses a qualitative approach with descriptive methods. In data collection, the writer uses interviewing and documentation techniques. The results of this study show that the strategy of the Government of Pekanbaru inining food resilience during the Covid-19 pandemic is the socialization of KWT/KT, building or providing governmental stimulus assistance in the field of food security for KWT /KT, monitoring of the distribution of aid to KWT, and evaluating the implementation of the Strategy of the Governments in keeping food security in the time of the COVID-19 Pandemic. As for the strategy carried out by the Department of Food Resilience, it is possible to know from the number of recipients of the program more safe food than those in the food vulnerability category. With regard to internal impediment factors, refocusing the budget due to the presence of the Covid-19 pandemic and external impediments, such as adaptation related to the understanding of KWT/KT activities, optimization of land utilization, lack of attention to KWT /KT, as well as lack of information obtained by KWT on the development of the Food Housing Area (KRPL) and the mining activities of Food Self-Government. (KAMAPAN). Keywords: Strategy, Distributing Food Security, Covid-19 Pandemic